Dual-Target Peptide-Modified Erythrocyte Membrane-Enveloped PLGA Nanoparticles for the Treatment of Glioma - Cui, Yuexin; Sun, Jiejie; Hao, Wenyan; Chen, Mengyu; Wang, Yingzi; Xu, Fenghua; Gao, Chunsheng (Frontiers in Oncology, 2020)
Penetration of the blood–brain barrier (BBB) and the blood–brain tumor barrier (BBTB) remains a significant challenge for the delivery of drugs in the treatment of glioma. Therefore, the development of targeted preparations with the ability to penetrate the BBB and BBTB, and target gliomas, is an important approach if we are to improve the efficacy of glioma treatment. In the current study, an active targeting preparation based on PLGA nanoparticles coated with erythrocyte membranes (RBCNPs) and dual-modified with DWSW and NGR peptide ligands (DWSW/NGR-RBCNPs). Euphorbia factor L1 (EFL1) extracted from euphorbiae semen was used as the model drug. The final nanoparticles were characterized by in vivo and in vitro tests. In vitro results showed that EFL1-loaded DWSW/NGR-RBCNPs were taken up by cells and had the ability to penetrate the BBB and BBTB and produce cytotoxic effects. Furthermore, in vivo studies in mice showed that when injected intravenously, these specialized NPs could enter the brain, target tumor tissue, and significantly extend life span. The results showed that dual-targeting EFL1-loaded DWSW/NGR-RBCNPs have significant potential as a nanotherapeutic tool for the treatment of brain glioma.